Damage identification in beams using additional rove mass and wavelet transform - Erwin U. L. Palechor; Luciano M. Bezerra; Marcus V. G. de Morais; Ramon S. Y. R. C. Silva (Fracture and Structural Integrity)
There is a need for efficient techniques that could identify damages in structures such as in bridges, pipelines, buildings, dams, among others. In order to carry out continuous monitoring of structures, this paper proposes a new experimental methodology for the identification of damages in steel beams. The methodology is based on the variation of the fundamental frequencies caused by the application of an extra additional mass along the length of the structure. This paper proposes the association of additional masses with wavelet transform in the processing of non-stationary signals and the realization of experimental tests on commercial profiles of steel beams under support conditions close to real situations. The experimental tests of simply supported steel beams are presented and discussed in this paper. The results show that the proposed methodology can identify damages or at least give a good indication of the region where damages might be.